Korelasi Tingkat Pengetahuan Pedagang Dengan Kepadatan Lalat Di Pasar Kampung Lalang Kota Medan - Nanda, Meutia; Nayla, Imsakina; Rahmanda, Lily; Sintia, Putri; Jawahir, Ainun; Ritonga, Syaira Alfauza (JUKEJ : Jurnal Kesehatan Jompa, 2025)
Environmental sanitation of traditional markets is an important aspect in preventing the development of disease vectors such as flies. This study aims to analyze the level of knowledge of traders regarding environmental sanitation and observe the density of flies in Kampung Lalang Market, Medan City. The study was conducted with an analytical observational design through a cross-sectional approach to 96 trader respondents. Data collection was carried out through questionnaires and direct observation using fly glue in three main locations of the market: temporary disposal sites (TPS), bathrooms/toilets, and fish trader areas. The results showed that the majority of traders (83%) had a good to very good level of knowledge regarding sanitation. However, observations showed that the highest fly density occurred in the TPS area, moderate in the fish trader area, and the lowest in the bathroom/toilets. These findings indicate that the high level of knowledge of traders has not been followed by adequate hygienic behavior practices and environmental management. Environments with high organic waste and poor waste management systems remain breeding grounds for flies. Therefore, an integrated approach is needed such as education on clean behavior, improvement of market sanitation infrastructure, and routine supervision to reduce the fly population and create a healthier market environment.